Pendidikan Islam di Masa Awal Kemerdekaan Indonesia: Peran Sejarah dalam Membentuk Identitas Pendidikan Nasional - Haq, Ihsan Abdul (PT. Student Rihlah Indonesia, 2025)
This research examines the strategic role of Islamic education in the early days of Indonesian independence in shaping the identity of national education. The main objective of this study is to reveal how the contribution of Islamic education institutions, Muslim figures, and post-independence government policies shaped the direction and character of Indonesian national education with religious, humanist, and nationalist characteristics. The methodology used is a historical qualitative approach with analysis of primary and secondary sources, such as state archives, educational documents, and the works of Islamic education figures. The results show that Islamic education has a central role in grounding the values of Pancasila and strengthening national integration through Islamic boarding schools, madrasas, and other Islamic educational institutions. The novelty of this research lies in the disclosure of historical dynamics that have received less attention in contemporary national education discourse. The implication for policy is the importance of reorienting education policy to better accommodate local and spiritual values that have proven to be the unifying force of the nation since the beginning of independence.